Coffee (Coffea spp.) Production Systems, Postharvest Innovations, and Quantitative and Agroecological Dynamics in the Davao Region, Philippines - Bautista, Cheryll L.; Valdez, Gemma M.; Erespe, Marites S.; Bastida, Garry L.; Magallones, Maria Odessa G.; Campo, Ruel G.; Pantoja, Felicitas B.; Nemenzo-Calica, Phoebe (Department of Agronomy and Horticulture, IPB University, 2026)
Coffee (Coffea spp.) is a globally significant tropical plantation crop, and the Davao Region in the Philippines is one of the country’s most dynamic production zones, thanks to its favorable volcanic soils, diverse microclimates, and evolving value chain ecosystems. With an estimated 15,821.68 ha under cultivation, the region supports all major Coffea species. Coffea arabica thrives above 1,000 m asl in highland zones such as Balutakay, Maragusan, and upland Davao City; Robusta dominates lower elevations, while Liberica and Excelsa occupy smaller areas as complementary tropical crop components. Agroecological sustainability is promoted through shade-based agroforestry systems that enhance biodiversity, soil fertility, and climate resilience. Postharvest innovations such as natural, honey, and micro-lot fermentation, alongside the expansion of community-based roasting facilities, have enabled specialty-grade production and improved access to premium domestic and international markets. Emerging trends presented at the Davao Regional Coffee Expo (DRCE) 2025 include the increased adoption of climate-resilient genetic varieties artificial intelligence-based plantation monitoring, gender-inclusive entrepreneurship, and youth participation in value-added roles such as roasting, cupping, and barista craftsmanship. However, persistent constraints, including aging plantations, low productivity, limited seedling supply, postharvest infrastructure gaps, market dependency on intermediaries, and inconsistent institutional support, continue to limit the sector’s tropical crop competitiveness. This status report consolidates insights on production systems, agroecological management, postharvest innovations, and socio-economic challenges to provide a strategic outlook for strengthening coffee as a sustainable tropical plantation crop within the Davao Region and similar highland environments in Southeast Asia.